Abdominal fat distribution in diffuse idiopathic skeletal hyperostosis and ankylosing spondylitis patients compared to controls. Issue 10 (October 2018) - Dan Lantsman, C.; Herman, A.; Verlaan, J.J.; Stern, M.; Mader, R.; Eshed, I.
Abstract : Aim: To evaluate abdominal fat distribution (subcutaneous adipose tissue [SAT] and visceral adipose tissue [VAT]) in two enthesopathy-related diseases with known correlation to metabolic syndrome (MS): diffuse idiopathic skeletal hyperostosis (DISH) and ankylosing spondylitis (AS) compared with controls. Materials and methods: Abdominal computed tomography (CT) examinations of 43 DISH (Resnick radiographic criteria) patients, 31 AS (Modified New York Criteria) patients and 42 age- and gender-matched (to DISH) controls (males: 29; 29; 27 and mean age: 71.7±7; 56.1±16; 72.7±8 years, respectively) were evaluated and compared for VAT and SAT surface areas on mid L3, L4, L5 levels. Results: AS patients were significantly younger compared to DISH patients and controls. No significant differences were observed between VAT and SAT of DISH and AS patients or between SAT values in all groups even after correction for age. VAT was higher in DISH and AS patients compared to controls on all three levels, but reached significance ( p< 0.05) only for DISH patients (L3: 24.34/23.6/18.43; L4: 23.85/22.21/18.05; L5: 19.09/18.94/14.24 mm 2, respectively). This did not change after correction for age. The VAT/SAT ratio was significantly larger in DISH and AS patients on all levels compared to controls. Conclusion: The higher VAT surface area, a known marker for MS, which by itself is associated with bone proliferation, in DISH and AS patients compared to controls substantiates its role as a potential surrogate marker for MS as well as suggests a potential shared pathogenic pathway for enthesopathic excessive bone production in DISH and AS. Highlights: Visceral fat surface area in DISH and ankylosing spondylitis is larger compared to controls. Visceral fat in entheses related diseases may be a biomarker for metabolic syndrome. Visceral fat in DISH and AS suggests a shared process of entheses bone production.